Self-Reported and Objectively Measured Physical Activity of Males from 50 to 69 Years Old - Jovan Radulovic (Journal of Anthropology of Sport and Physical Education)
The main goal of this study was to check the physical activity of men aged 50 to 69 years. The research involved 100 of them, where they were divided into two subunits, of which the first subunit was composed of 73 men, aged 50 to 59, and the second sub-adult of 27 men, who had between 50 and 69 years of age. A longer version of the international IPAQ questionnaire was used as the measuring instrument of this research, which contained four types of physical activity (business, transportation, household and leisure) through three levels of physical activity (low, medium and moderate). The results showed that physical activity in free time is not sufficiently represented, and that leisure time for recreation purposes is significantly less than expected. Likewise, physical activities for the purpose of transport are significantly lower than expected. The research has proven that the younger sub-examinees of the respondents are more physically active than the elderly, which is due to the fact that the physical activity of elderly people has been declining over the years.